Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

After going through all of your expenses for the month, you can up with the expression -2(x+3) – 5(2x – 7). Simplify the expression to represent your monthly expenses. Show your work.

Sagot :

SmPro

Answer:

-12x+29

Step-by-step explanation:

= -2(x+3) – 5(2x – 7)

= -2(x)+(-2)(3)-5(2x)-5(-7)

= -2x-6-10x+35

= -2x-10x-6+35

= -12x+29

Answer:  -12x+29

Step-by-step explanation:

monthly expenses=m

-2(x+3)-5(2x-7)=m

-2x-6-10x+35=m

-12x+29=m

that is answer simplified